Phylogenetic distribution of malonate semialdehyde decarboxylase (MSAD) genes among strains within the genus Mycobacterium: evidence of MSAD gene loss in the evolution of pathogenic mycobacteria - Lee, Duhyung; Kim, Dong Hyun; Seo, Hyejun; Choi, Seaone; Kim, Bum-Joon (Frontiers in Microbiology, 2023)
Despite the great diversity of malonate semialdehyde decarboxylases (MSADs), one of five subgroups of the tautomerase superfamily (TSF) found throughout the biosphere, their distribution among strains within the genus Mycobacterium remains unknown. In this study, we sought to investigate the phylogenetic distribution of MSAD genes of mycobacterial species via genome analysis of 192 different reference Mycobacterium species or subspecies retrieved from NCBI databases. We found that in a total of 87 of 192 strains (45.3%), MSAD-1 and MSAD-2 were distributed in an exclusive manner among Mycobacterium species except for 12 strains, including Mycobacterium chelonae members, with both in their genome. Of note, Mycobacterium strains better This is a provisional file, not the final typeset article adapted to the host and of high virulence potential, such as the Mycobacterium tuberculosis complex, Mycobacterium leprae, Mycobacterium marinum, Mycobacterium ulcerans and Mycobacterium avium subsp. paratuberculosis, had no orthologs of MSAD in their genome, suggesting MSAD loss during species differentiation in pathogenic slow-growing Mycobacterium. To investigate the MSAD distribution among strains of M. avium subspecies, the genome sequences of a total of 255 reference strains from the four subspecies of M. avium (43 of subspecies avium, 162 of subspecies hominissuis, 49 of subspecies paratuberculosis, and 1 of subspecies silvaticum) were further analyzed. We found that only 121 of 255 strains (47.4%) had MSADs in their genome, with none of the 49 M. avium subsp. paratuberculosis strains having MSAD genes. Even in 13 of 121 M. avium strains with the MSAD-1 gene in their genome, deletion mutations in the 98 th codon causing premature termination of MSAD were found, further highlighting the occurrence of MSAD pseudogenization during species or subspecies differentiation of M. avium. In conclusion, our data indicated that there are two distinct types of MSADs, MSAD-1 and MSAD-2, among strains in the Mycobacterium genus, but more than half of the strains, including pathogenic mycobacteria, M. tuberculosis and M. leprae, have no orthologs in their genome, suggesting MSAD loss during host adaptation of pathogenic mycobacteria. In the future, the role of two distinct MSADs, MSAD-1 and MSAD-2, in mycobacterial pathogenesis or evolution should be investigated.